MEMBANGUN EKONOMI PERKOTAAN MELALUI URBAN FARMING: STRATEGI PENINGKATAN VOLUME PRODUKSI DAN VALUE ADDED PRODUCT - Sarasmitha, Citra; Dalulia, Primahasmi; Sulistyorini, Ery; Gunawan, Szabyna Regytha Aura; Putra, Muhammad Afif Nur (Universitas Mataram, 2024)
Urban farming activities carried out by the Genitri 09 Farmers Group in Pisang Candi Village, Malang City, show that this group has succeeded in utilizing limited land for vegetable and fruit cultivation, including innovations in processing pakcoy mustard greens into ice cream (Sajiwi) as a value-added strategy. However, the main challenge faced is the low production capacity due to limited labor and manual production methods. To overcome this problem, the community service team offers a solution in the form of appropriate technology, namely ice cream maker, which is expected to be able to increase the efficiency and production capacity of Sajiwi. In addition to the procurement of machines, the service team also provides training to partners and ensures mutual understanding through focused discussion activities (FGD), in order to avoid misunderstandings and increase the success of the program.